Physiological and performance responses of sprint interval training and endurance training in Gaelic football players - Kelly, D. T.; Cregg, C. J.; O`Connor, P. L.; Cullen, B. D.; Moyna, N. M. (European Journal of Applied Physiology, 2021)
Purpose: While ideal for developing aerobic capacity, traditional endurance training (ET) is extremely time-consuming and may lack the specificity to maintain indices of speed and power in team sport athletes. In contrast, low-volume short-duration sprint interval training (SIT) has been shown to improve V.O2max to a similar extent as ET. However, to date, few studies have compared the effects of running-based SIT and ET, on aerobic capacity and indices of speed and power of trained team sport athletes. Methods: Club level male Gaelic football players were randomly assigned to SIT (n = 13; 26.5 ± 4.87 years) or ET (n = 12; 25.4 ± 2.58 years) groups. Participants trained 3 days week-1 for 6 weeks. V.O2max, RE, vV.O2max, blood lactate concentrations, Wingate test performance, running speed, jump performance and intermittent endurance performance (IEP) were measured at baseline and after 6 weeks. Results: An increase in V.O2max (p < 0.05), vV.O2max (p < 0.001) and IEP (p < 0.001) following 6 weeks of both SIT and ET was observed. Wingate mean power (p < 0.001), peak power (p < 0.001) and fatigue index (p < 0.005) were all significantly improved following training in both groups. Velocity at LT was significantly higher and performance in the 20-m running speed and VJ tests were significantly reduced post training in the ET group (all p < 0.005). Conclusion: Despite the large difference in total training time, a running-based protocol of SIT is a time efficient training method for improving aerobic capacity and IEP while maintaining indices of lower body power and running speed in team-sport players.